2015
DOI: 10.1021/acs.organomet.5b00564
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of New (η5-Cyclopentadienyl)dicarbonylruthenium(II) Amine Complexes: Their Application as Homogeneous Catalysts in Styrene Oxidation

Abstract: The water-soluble ruthenium(II) mononuclear complexes [CpRu(CO) 2 NH 2 R]BF 4 (Cp = η 5 -C 5 H 5 ; R = C 6 H 11 (1), C 6 H 5 (2), CH 2 C 6 H 5 (3), CH(CH 3 )C 6 H 5 (4), CH 2 (C 6 H 4 O)CH 3 (5), CH 2 (C 6 H 4 )CN ( 6), C 6 H 2 (CH 3 ) 3 (7), CH 2 CHCH 2 (8), CH(CH 3 ) 2 ( 9)) were synthesized from the reaction of the organometallic Lewis acid [CpRu(CO) 2 ]BF 4 with amine ligands at room temperature. These complexes are reported for the first time and have been fully characterized by IR, high-resolution mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The N-Ru-N bond angle is 76.90(5)°. The N-Ru-Cl bond angles range was 82.05(3)-88.41(3)°like in related compounds [7][8][9][10]. The water and the perchlorate anion are both involved in O-H· · · O hydrogen bonds.…”
Section: Discussionmentioning
confidence: 95%
“…The N-Ru-N bond angle is 76.90(5)°. The N-Ru-Cl bond angles range was 82.05(3)-88.41(3)°like in related compounds [7][8][9][10]. The water and the perchlorate anion are both involved in O-H· · · O hydrogen bonds.…”
Section: Discussionmentioning
confidence: 95%
“…They stabilize and protect the metal centre and thereby prevent rapid oxidation of the Ru(II) to Ru(III) [4]. The title compound is part of our continuing studies of half-sandwich ruthenium(II) complexes [5][6][7][8], in which the cationic species of the complex feature the known "pseudooctahedral three-legged piano stool" structure. As expected, the ruthenium centre is coordinated to the N,N′-bidentate ligand through the nitrogen atoms and the chlorido ligand and the three atoms serve as the base of the piano stool.…”
Section: Discussionmentioning
confidence: 99%
“…16 Therefore, converting styrene into any value-added material is highly advantageous. In the past, numerous works reported for the oxidation of styrene with a ligand-based catalyst, 17 a nonmetallic catalyst, 18 a metallic catalyst, 19 and molecular sieves. 20 Cancino et al demonstrated a Cu-based homogeneous catalyst with 61% styrene conversion and 26% benzaldehyde selectivity.…”
Section: Introductionmentioning
confidence: 99%